Polyunsaturated Fatty Acid and S-Adenosylmethionine Supplementation in Predementia Syndromes and Alzheimer's Disease: A Review - Francesco Panza; Vincenza Frisardi; Cristiano Capurso; Alessia D'Introno; Anna M. Colacicco; Alessandra Di Palo; Bruno P. Imbimbo; Gianluigi Vendemiale; Antonio Capurso; Vincenzo Solfrizzi (The Scientific World Journal)
A growing body of evidence indicates that nutritional supplements can improve cognition; however, which supplements are effective remains controversial. In this review article, we focus on dietary supplementation suggested for predementia syndromes and Alzheimers disease (AD), with particular emphasis on S-adenosylmethionine (SAM) and polyunsaturated fatty acids (PUFA). Very recent findings confirmed that SAM can exert a direct effect on glutathione S-transferase (GST) activity. AD is accompanied by reduced GST activity, diminished SAM, and increased S-adenosylhomocysteine (SAH), the downstream metabolic product resulting from SAM-mediated transmethylation reactions, when deprived of folate. Therefore, these findings underscored the critical role of SAM in maintenance of neuronal health, suggesting a possible role of SAM as a neuroprotective dietary supplement for AD patients. In fact, very recent studies on early-stage AD patients and moderate- to late-stage AD patients were conducted with a nutriceutical supplementation that included SAM, with promising results. Given recent findings from randomized clinical trials (RCTs) in which n-3 PUFA supplementation was effective only in very mild AD subgroups or mild cognitive impairment (MCI), we suggest future intervention trials using measures of dietary supplementation (dietary n-3 PUFA and SAM plus B vitamin supplementation) to determine if such supplements will reduce the risk for cognitive decline in very mild AD and MCI. Therefore, key supplements are not necessarily working in isolation and the most profound impact, or in some cases the only impact, is noted very early in the course of AD, suggesting that nutriceutical supplements may bolster pharmacological approaches well past the window where supplements can work on their own. Recommendations regarding future research on the effects of SAM or n-3 PUFA supplementation on predementia syndromes and very mild AD include properly designed RCTs that are sufficiently powered and with an adequate length (e.g., 3–5 years of follow-up).